Acknowledgement & Editor's Note - CJAL Editorial Board (Columbia Journal of Asian Law, 1987)
ACKNOWLEDGMENT The Journal of Chinese Law gratefully acknowledges the generous grant from the Parker School of Foreign and Comparative Law which made establishment of the Journal possible. EDITORS' NOTE The Journal of Chinese Law will follow the pinyin system of transliterating Chinese into English. Pinyin is the system currently in use in the People's Republic of China where publishers adopted it on January 1, 1979 in response to a decision of the State Council. Methods other than pinyin will be used when a certain version of a Chinese proper noun has achieved widespread currency in English or when the title of or excerpt from a publication in a language other than Chinese incorporates a non-pinyin spelling.